Cognitive behavioural group therapy for social phobia with or without attention training: A controlled trial - McEvoy, Peter; Perini, S. (Pergamon, 2009)
The Self-Regulatory Executive Function model [S-REF; Wells, A., & Matthews, G. (1996). Modellingcognition in emotional disorder: the S-REF model. Behaviour Research and Therapy, 34, 881–888] proposes that metacognitive beliefs, inflexible self-focused attention, and perseverative thinking (rumination and worry) play an important role in maintaining emotional dysfunction. Attention training [ATT; Wells, A. (1990). Panic disorder in association with relaxation induced anxiety: an attentional training approach to treatment. Behavior Therapy, 21, 273–280] is a technique designed to increase attentional control and flexibility, and thereby lessen the impact of these maintaining factors. The main aim of this study was to determine whether or not supplementing cognitive behavioral group therapy (CBGT) with ATT could potentiate greater changes in social anxiety, depression, attentional control, metacognitive beliefs, and anticipatory and post-event processing in a clinical sample with social phobia. Patients (N = 81) were allocated to CBGT with ATT or relaxation training (RT). ATT did not potentiate greater change on any outcome variable, with both groups achieving significant improvements on all measures. Exploratory correlational analyses (pre-treatment and changes scores) showed that somemetacognitive beliefs were associated with attentional control, anticipatory processing, and symptoms of social anxiety and depression. However, attentional control was more consistently associated with anticipatory processing, post-event processing, and symptoms of social anxiety and depression, than with metacognitive beliefs. Results are discussed with reference to cognitive behavioral models of social phobia. It is tentatively concluded that while supplementing CBGT with ATT does not improve outcomes, increasing attentional control during CBGT is associated with symptom relief.